2010
DOI: 10.1111/j.1440-172x.2009.01801.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a health education programme on healthy lifestyles and practices among university students

Abstract: This study aimed at exploring the lifestyles of university students, the relationship between specific demographical variables and health practices and the role of training in improving these practices. An experimental and a comparison group were selected using the convenient sampling method. Two 5-day training programmes on healthy lifestyles were conducted. Self-reported behaviours of both groups were assessed before and after the programme. The results reflected slightly positive health practices related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 20 publications
1
31
1
Order By: Relevance
“…Being physically active and eating healthily are known to reduce the risk of developing noncommunicable diseases such as cancer, cardiovascular disease, obesity, and type 2 diabetes [1]. Few young people, however, reach the recommendations of health behavior for the prevention of noncommunicable diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being physically active and eating healthily are known to reduce the risk of developing noncommunicable diseases such as cancer, cardiovascular disease, obesity, and type 2 diabetes [1]. Few young people, however, reach the recommendations of health behavior for the prevention of noncommunicable diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to foster a healthy lifestyle in university students are therefore essential. Some evidence reveals that multiple behavior health interventions can promote both exercise and healthy diets in university students [1,7,8]. Thus, behavioral interventions for university students are required to support long-lasting behavior changes beyond late adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has tended to focus on health-promoting behaviours in university students who are single, younger (17-25 years), financially supported by their families (Al-Kandari & Vidal, 2007;Peker & Bermek, 2011), and who study on campus in a health-related field such as nursing (Abdu-Moghli, Khalaf, & Barghoti, 2010;Al-Kandari & Vidal, 2007;Al-Kandari, Vidal, & Thomas, 2008;Haddad, Kane, Rajacich, Cameron, & Al-Ma'aitah, 2004). Few studies have examined health-promoting behaviours in older students (ie, over 25 years), who are studying at a distance and from off-campus, and yet this student demographic has been expanding in most universities in Australia as well as elsewhere.…”
mentioning
confidence: 99%
“…Another Jordanian study by Ammouri (2008) [21] revealed that a small percentage of Jordanian adults participated in health promoting behaviors and that demographic factors such as gender, age, and income are important determinant of the individual engagement in the health promoting behaviour. A study by Abu-Mogli et al (2010) [22] that examined the effect of five days education program on type of diet, physical activity and nutritional habit revealed that there was a positive influence of training on improving health behaviors of university students related to the three behavioral categories.…”
Section: Introductionmentioning
confidence: 99%